INOVASI E-SIMPEL DALAM PENINGKATAN PELAYANAN KEPENDUDUKAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN GROBOGAN - Lolitasari, Aliza; Maesaroh, Maesaroh; Widowati, Nina (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The e-Simpel innovation is an online-based population document service and is useful in making it easier for people to process population documents. This research aims to analyze e-Simpel innovation and identify the factors driving and inhibiting innovation in improving population services at the Grobogan Regency Population and Civil Registration Department. This research uses the theory of innovation attributes according to Everett M. Rogers, namely relative advantage, suitability, complexity, possibility of being tried, and ease of observation. Meanwhile, according to Harrington Emerson, the driving and inhibiting factors are Man, Money, Materials, Machine, Methods. The research method used is a qualitative descriptive method with data collection techniques through interviews, observation and documentation. The results of research on the implementation of e-Simpel innovation can be seen from the benefits felt by the community in the form of comfort and satisfaction. Judging from the suitability of community needs, values and norms, and in accordance with previous services. Judging from the possibilities, it can be observed in the form of an easy mechanism and cost and time efficiency. The complexity attribute is server problems and low community participation. Judging from the possibilities of being tried, socialization has not yet spread widely. Apart from that, there are driving factors in the form of employees and infrastructure. Meanwhile, inhibiting factors include budget, technology and procedures. In improving e-Simpel innovation, it is recommended that management simplify the process of using e-Simpel, carry out application maintenance and carry out massive outreach.